The role of project management in achieving the sustainable development of smart cities - Abdul Razzak Alshehadeh; Fuad A. Al-Bataineh; Ahmad MohD Ababneh; Baker Akram Falah Jarah; Haneen A. Al-khawaja (Journal of Project Management)
Integrating project management (PM) and sustainable development (SD) is not merely an option but a necessity for smart cities (SC) to secure a prosperous future for the next generations. Also, useful PM plays a vital role in fostering sustainable growth within SC, as it enhances the quality of life, conserves natural resources, and encourages technological creation. Therefore, this study aimed to examine the significance of PM in advancing the SD of SC. Randomly 189 questionnaires were distributed to possible respondents working in PM by email, hardcopy mailings, and web-collection apps. The statistical analysis was carried out using SPSS version 25, by using a quantitative research approach. The results showed that all study variables (smart technologies company policies, resource management, and organizational culture) positively impacted smart cities' SD. Therefore, the study recommends enhancing the incorporation of PM and SD in SC by implementing effective processes and technologies that connect harmoniously with technological advancement and environmental and social sustainability.